Property, Kinship and Cultural Capital: The Ethics of Modelling Kinship in Sustainable Resource Management - Wiber, Melanie G.; Lovell, Peter (Anthropologica, 2022)
This paper originated in the theoretical, methodological and ethical issues raised by the possibility of formally mapping kin-based rights in resources using new developments in GIS and data management software. While acknowledging that there are valuable applications for such mapping exercises in Native land claims or other battles over local rights in natural resources, we argue that the proliferation of such formal mapping methods raise a number of pressing concerns. One concern is the resurgence of simplistic functionalist arguments as with the concept of cultural capital, utilized in some publications on adaptive management and in community based natural resource conservation. Another concern is the implicit reliance on overstructuralist modelling of non-Western kinship systems. Salient ethical questions concern the possible dangers of "making legible" to the state legal systems such highly formalized and thus static kinship models.